Impact of endogenous glucocorticoid on response to immune checkpoint blockade in patients with advanced cancer - Cui, Yu; Han, Xinyue; Liu, Hongtao; Xie, Qi; Guan, Yaping; Yin, Beibei; Xiao, Junjuan; Feng, Dongfeng; Wang, Xuan; Li, Junwei; Chen, Jinghua; Liu, Xiaolin; et al. (Frontiers in Immunology, 2023)
Background: Previous studies indicate that exogenous use of glucocorticoid (GC) affects immune checkpoint inhibitor (ICI) efficacy. However, there is a paucity of clinical data evaluating the direct impact of endogenous GC on the efficacy for cancer patients with immune checkpoint blockade. Methods: We first compared the endogenous circulating GC levels in healthy individuals and patients with cancer. We next retrospectively reviewed patients with advanced cancer with PD-1/PD-L1 inhibitor alone or combination therapy in a single center. The effects of baseline circulating GC levels on objective response rate (ORR), durable clinical benefit (DCB), progression‐free survival (PFS), and overall survival (OS) were analyzed. The association of the endogenous GC levels with circulating lymphocytes, cytokines levels, and neutrophil to lymphocyte ratio, and tumor infiltrating immune cells, were systematically analyzed. Results: The endogenous GC levels in advanced cancer patients were higher than those in early-stage cancer patients as well as healthy people. In the advanced cancer cohort with immune checkpoint blockade (n=130), patients with high baseline endogenous GC levels (n=80) had a significantly reduced ORR (10.0% vs 40.0%; p<0.0001) and DCB (35.0% vs 73.5%, p=0.001) compared to those with low endogenous GC levels (n=50). The increased GC levels was significantly associated with reduced PFS (HR 2.023; p=0.0008) and OS (HR 2.809; p=0.0005). Moreover, statistically significant differences regarding PFS, and OS were also detected after propensity score matching. In a multivariable model, the endogenous GC was identified as an independent indicator for predicting PFS (HR 1.779; p=0.012) and OS (HR 2.468; p=0.013). High endogenous GC levels were significantly associated with reduced lymphocytes (p=0.019), increased neutrophil to lymphocyte ratio (p=0.0009), and increased interleukin-6 levels (p=0.025). Patients with high levels of endogenous GC had low numbers of tumor infiltrating CD3+ (p=0.001), CD8+ T (p=0.059), and CD4+ T (p=0.002) cells, and the numbers of circulating PD-1+ NK cells (p=0.012), and the ratio of CD8+PD-1+ to CD4+PD-1+ (p=0.031) were higher in patients with high levels of endogenous GC compared to low levels of endogenous GC. Conclusion: Baseline endogenous GC increase executes a comprehensive negative effect on immunosurveillance and response to immunotherapy in real-world cancer patients accompanied with cancer progression.